Frenglish in Quebec English Newspapers - Fee, Margery (Papers from the Annual Meetings of the Atlantic Provinces Linguistic Association (PAMAPLA) / ACTES DES COLLOQUES ANNUELS DE L’ASSOCIATION DE LINGUISTIQUE DES PROVINCES ATLANTIQUES (ACAALPA)., 1992)
The paper examines gallicisms, mainly lexical, in the Montreal Gazette (1 editorial 1988; 7 issues 1989) and in the Quebec City Chronicle-Telegraph (23 issues 1991). The findings are compared to those of an earlier examination of gallicisms in the same newspapers (Manning and Eatock 1982; Roberts 1983). Problems with the traditional methodology are examined. Consideration is given to the concepts evolved by sociolinguists studying the influence of English on Canadian French, by sociologists of language and by those studying the relations between society and culture. Halliday's model of language as a social semiotic is suggested as a counterbalance to Weinreich's structural-communicational model.